From ideal occlusion to dentofacial deformity and back to ideal: an osteochondroma treatment with lingual orthodontics - Martins, Renato Parsekian [UNESP] (2017)
This original case report describes the morphologic changes caused by a mandibular condylar osteochondroma (OC) on a female patient and its treatment. The changes were identified by comparing her final records from a previous orthodontic treatment, without the presence of OC, to records taken before a second treatment, with a developed OC. The diagnostics and treatment for the OC and its consequences were described and discussed in this paper. Treatment included orthodontics with a lingual appliance, low condylectomy on the affected side, high condylectomy on the contralateral side, bilateral disc repositioning and orthognathic surgery. It was concluded that the OC caused a Class III subdivision malocclusion, midline deviation and an edge-to-edge bite on the left side, a cant of the occlusal plane on the Z-axis and a deviation of the pogonion to the left. Treatment was successful and stable long term (36 months) with good occlusal, aesthetical and functional results.